Comparative Diagnostic Accuracy of Appendicitis Inflammatory Response and Alvarado Scores in Adult Appendicitis - Sawsan Hanafi; Noura Alshareef; Wesam Edrees; Jamil M. Baljoon; Faris Salah Abunar (Saudi Journal of Emergency Medicine)
Background Acute appendicitis is a common surgical emergency, with diagnostic challenges that can lead to unnecessary surgeries. This study aims to compare the diagnostic accuracy of the Appendicitis Inflammatory Response (AIR) score and the Alvarado score in a clinical setting, examining the influence of demographic variables on their performance.